2018
DOI: 10.1126/sciadv.1602170
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of endosomes demonstrates coordination of molecular motors during axonal transport

Abstract: Multipolarization microscopy shows tight linkage of the rotational dynamics of axonal endosomes to molecular motor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 42 publications
3
57
1
Order By: Relevance
“…Instead, it is an active rotation driven by motor proteins as they coordinate to navigate through microtubule intersections. Cargos exhibited increased rotation at pauses in our study, which is different from observations by Kaplan et al that cargo rotation in axons is constrained at pauses (24). This discrepancy is possibly due to the different geometry of microtubules in Vero cells and axons.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Instead, it is an active rotation driven by motor proteins as they coordinate to navigate through microtubule intersections. Cargos exhibited increased rotation at pauses in our study, which is different from observations by Kaplan et al that cargo rotation in axons is constrained at pauses (24). This discrepancy is possibly due to the different geometry of microtubules in Vero cells and axons.…”
Section: Discussioncontrasting
confidence: 99%
“…Gu et al showed that cargos rotate in axons because of partial detachment from microtubules (22). Kaplan et al in a very recent study also used gold nanorod probes to demonstrate that cargo rotation in axons increases during transient reversals of transport (24). Our group recently demonstrated that rod-shaped phagosomes rotate both in-plane and longitudinally as they are transported in cells (25).…”
Section: Introductionmentioning
confidence: 94%
“…Recent measurements observed rotational motion in the trajectories of endosomal cargos carrying gold nanorods. 30 In addition, correlative live-cell and super-resolution microscopy showed that rotational movement could be used by cargos to avoid steric obstacles. 29 These studies proposed that rotational movement and off-axis stepping might result from having a mix of motors, such as kinesin-2 or dynein, on the cargo along with kinesin-1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that rotation of a cargo around the MT requires the presence of both kinesin and dynein motors on the cargo or the distortion of the lipid cargo. 26,29,30 To test whether a single type of motor can rotate a rigid cargo around the MT, we tracked beads driven by multiple kinesins or dyneins on MT bridges. If the beads were positioned below the MT when they reached the end of the bridge, they were challenged to bypass the PDMS wall ( Fig.…”
Section: Multi-motor Cargos Rotate Around the Mt To Avoid Large Obstamentioning
confidence: 99%
“…When (47,48). In these GNR-containing early endosomes, the GNR is wrapped tightly by the membrane and show no significant movement relative to the vesicle, which meets the criterion for rotational tracking (16).…”
Section: Resultsmentioning
confidence: 84%